Effect of salvage market on strategic technology choice and capacity investment decision of firm under demand uncertainty - Kashefi, Mohammad Ali (Journal of Business Economics and Management, 2016)
This paper examines the effect of salvage market on technology choice and capacity investment decision of two firms that compete on quantity under demand uncertainty. A game theoretic model applies such that firms choose their production technology between two alternatives: flexible versus inflexible production process. Then they decide on the amount of capacity investment: flexible firm makes decision about general and specific components and inflexible firm just about unified component. One stage forward both enter the primary market in which demand is uncertain and play a la Cournot and finally, flexible firm will be able to sell its unsold general components in the secondary market with a deterministic price. Numerical study was employed to observe equilibrium behavior of firms. Findings demonstrate that with symmetric parameterization there is a unique Nash equilibrium in which both firms choose inflexible technology while applying asymmetric parameters has the potential to form two types of equilibrium when both firms choose inflexible technology or only one firm chooses flexible technology. Moreover, it is shown that there is a cost threshold that could shift the equilibria.